Política e assistencialismo na Paraíba: o governo de José Américo de Almeida (1951-1956). - Barbosa, Jivago Correia (2012)
Through this research, in development with the Pos-Graduate Program in History/UFPB, I approach the government of José Américo de Almeida (1951-1956), elected by direct vote after a fierce political campaign in Paraíba. I settled this issue, because it is a subject little explored by the historiography of Paraiba. The fundamental questions that guide this work are the political circumstances in which José Américo ascends to power in 1950, the violent election, considered one of the most radical and bloody campaigns have disputed in Paraiba, where among the many clashes between supporters and militants of PSD and UDN, we will emphasize the fateful episode of Bandeira Square (Praça da Bandeira), in Campina Grande, because it was an event that gained space in various media at the regional and national level, analyzing the reasons that caused the conflict, the phenomenon of drought of 1951-52 drought and its effects for the northeastern states and, in particular, in Paraíba, the re-establishment of drought industry in the state of Paraiba through policies to combat the drought - especially hydraulic solutions, construction and paving of roads - introduced by Jose Américo over this period, such measures to avoid, according to the governor, the population movements that had already occurred largely since the year 1950. Throughout our work we show that the homily of the "great minister in 1932" seems contradictory and dubious at the same time as the construction of dams, paving and construction of roads were inserted into a political project "of support for flagellate populations, "why not benefit from all the cities affected by the effects of drought, instead of favoring some cities and districts - politically allied to the" americismo "- at the expense of others? As background for this discussion, we will analyze the role of the newspaper A União - official press organ of the largest circulation throughout the state - which has spread the view that the dams would become the best solution to the problem of dry. For this work, besides the use of secondary literature, were analyzed and observed some major news regarding the Government, found in the newspaper A União. We also searched the Public File of the State which is in the Espaço Cultural (Cultural Center), the Casa Jose Américo de Almeida Foundation and the private library of Mr. Maurilio de Almeida.